CPPU may induce gibberellin-independent parthenocarpy associated with PbRR9 in 'Dangshansu' pear. (1st May 2020) - Cong, Liu; Wu, Ting; Liu, Hanting; Wang, Huibin; Zhang, Haiqi; Zhao, Guangping; Wen, Yao; Shi, Qianrong; Xu, Lingfei; Wang, Zhigang
Abstract: Parthenocarpy is a valuable trait in self-incompatible plants, such as pear. N -(2-chloro-4-pyridyl)- N' -phenylurea (CPPU), a synthetic cytokinin analog, can induce parthenocarpy in pear ( Pyrus spp.), but the mechanism of induction is unclear. To investigate the role of gibberellin in CPPU-induced parthenocarpy in pear, CPPU supplemented with paclobutrazol (PAC) was sprayed onto 'Dangshansu' pear. We found that the fruit set rate of pear treated with CPPU supplemented with PAC was identical to that in a CPPU-alone treatment group. In regard to cell development, CPPU mainly promoted hypanthium cell division and expansion, and PAC application had no influence on CPPU-induced cell development. RNA sequencing revealed that gibberellin 20 oxidase and gibberellin 3 oxidase genes were not differentially expressed following CPPU treatment. According to the analysis of fruit phytohormone content, the CPPU treatments did not induce gibberellin biosynthesis. These results suggest that CPPU-induced parthenocarpy may be gibberellin independent in 'Dangshansu' pear. After CPPU treatment, the indole acetic acid (IAA) content in fruit was significantly increased, and the abscisic acid (ABA) content was significantly decreased. Similarly, RNA sequencing revealed that many genes involved in the auxin and ABA pathways were significantly differentially expressed in the CPPU treatment groups; among them, indole-3-pyruvate monooxygenase ( YUCCA ) was significantly upregulated and 9-cis-epoxycarotenoid dioxygenase ( NCED ) was significantly downregulated. IAA and ABA may thus play important roles in CPPU-induced parthenocarpy. PbTwo-component response regulator9 ( PbRR9 ), PbYUCCA4, and PbNCED6 were then selected to further elucidate the mechanism of CPPU-induced parthenocarpy. A yeast one-hybrid assay indicated that PbRR9 can combine with the PbYUCCA4 and PbNCED6 promoters. Dual luciferase assays revealed that PbRR9 can promote and repress the activities of the PbYUCCA4 and PbNCED6 promoters, respectively. After the transient expression of PbRR9 in fruits, PbYUCCA4 expression was significantly upregulated, and PbNCED6 expression was significantly downregulated. This study uncovered a CPPU-induced parthenocarpy mechanism that is different from that in tomato. CPPU may upregulate PbYUCCA4 and downregulate PbNCED6 by upregulating PbRR9, thereby increasing IAA content and decreasing ABA content to ultimately induce parthenocarpy in 'Dangshansu' pear. However, because only a single time point was used and because 'botanical' and 'accessory' fruits have different structures, this conclusion is still preliminary.